Seed germination and dormancy traits of forbs and shrubs important for restoration of North American dryland ecosystems - Kildisheva, O.; Erickson, T.; Madsen, M.; Dixon, Kingsley; Merritt, D. (2018)
© 2018 German Society for Plant Sciences and The Royal Botanical Society of the Netherlands In degraded dryland systems, native plant community re-establishment following disturbance is almost exclusively carried out using seeds, but these efforts commonly fail. Much of this failure can be attributed to the limited understanding of seed dormancy and germination traits. We undertook a systematic classification of seed dormancy of 26 species of annual and perennial forbs and shrubs that represent key, dominant genera used in restoration of the Great Basin ecosystem in the western United States. We examined germination across a wide thermal profile to depict species-specific characteristics and assessed the potential of gibberellic acid (GA3) and karrikinolide (KAR1) to expand the thermal germination envelope of fresh seeds. Of the tested species, 81% produce seeds that are dormant at maturity. The largest proportion (62%) exhibited physiological (PD), followed by physical (PY, 8%), combinational (PY + PD, 8%) and morphophysiological (MPD, 4%) dormancy classes. The effects of chemical stimulants were temperature- and species-mediated. In general, mean germination across the thermal profile was improved by GA3 and KAR1 for 11 and five species, respectively. We detected a strong germination response to temperature in freshly collected seeds of 20 species. Temperatures below 10 °C limited the germination of all except Agoseris heterophylla, suggesting that in their dormant state, the majority of these species are thermally restricted. Our findings demonstrate the utility of dormancy classification as a foundation for understanding the critical regenerative traits in these ecologically important species and highlight its importance in restoration planning.